Assessment of right ventricular function after successful percutaneous coronary intervention to chronic total occlusion using different echo-Doppler modalities - Eman R Zaki (Wolters Kluwer Medknow Publications, 2021)
Background and aim Chronic total occlusion is a common condition in patients with coronary artery disease and represents one of the most challenging targets of lesion recanalization with successful percutaneous coronary intervention (PCI). Different echo-Doppler modalities can be used for the assessment of right ventricular (RV) performance in patients undergoing PCI with reported superiority of the newer modalities. The aim was to assess the effect of successful PCI for chronic totally occluded vessel on the RV performance by different echo-Doppler modalities. Patients and methods The present study enrolled 25 patients with chronic total occlusion for whom PCI was performed. Patients were subjected to history taking, clinical assessment, 12-lead surface ECG, and evaluation of RV functions before, within 48 h after successful PCI, and 1 month later, using conventional and new echo-Doppler modalities. Echo-Doppler parameters included RV dimensions, Doppler flow velocities (E, A, and E/A) across tricuspid valves, RV fractional area change (RV-FAC), tricuspid annular plane systolic excursion, tissue Doppler systolic, and diastolic velocities (Sa, Ea, and Aa) at the lateral tricuspid annulus, in addition to evaluation of RV global longitudinal strain (RV-GLS). Results There was no significant improvement of parameters reflecting RV function comparing the pre-PCI and 48-h post-PCI values. On the contrary, significant improvement was detected comparing the echo-Doppler measures of either the pre- or 48-h PCI value with those of 1 month later. There was a significant increase of RV-FAC, tricuspid Sa and Ea, and RV-GLS (P<0.05). The E/A ratio of tricuspid flow and tricuspid annular plane systolic excursion showed no significant difference from pre- to 48 hr or 1-month PCI value. Conclusion RV performance improves after successful PCI of chronic totally occluded vessels. Newer echo-Doppler modalities appear to be better tools for assessment of RV performance.